EXOGENOUS APPLICATION OF PLANT GROWTH REGULATORS ON GENETIC DIVERSITY OF WHEAT TO ACCOMPLISH THE OPTIMUM PRODUCTION UNDER LATE SOWN CONDITIONS - Sami Ullah; Mohammad Safdar Baloch; Muhammad Amjad Nadeem; Asghar Ali Khan; Qudrat Ullah Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Wheat yield in Pakistan is low on account of various biotic and abiotic stressors. Late sowing of wheat after harvesting of cotton, rice, and sugarcane crops is considered as the main cause of low yield in the country. The delayed physiological maturity and terminal heat stress are the main contributors to this yield decline. The appropriate use of plant growth regulators (PGRs) and selection of suitable varieties may help to alleviate these stresses. A field experiment was conducted at Pakistan Agricultural Research Council, Arid Zone Research Centre (AZRC), Dera Ismail Khan, Khyber Pakhtunkhwa (KP) Province, Pakistan on late sown wheat for two successive years (2019-2020 and 2020-2021). The experiment was comprised of different combinations of plant growth regulators-PGRs (viz. Amino Acids-AA + Gibberellic Acid-GA, GA + Potassium-K, K + AA, AA + GA + K and control), and wheat varieties i.e. AZRC Dera (long duration) and Paseena (short duration) sown on 10th December and 10th January in a randomized complete block design with factorial arrangements. The maximum plant height, chlorophyll content (i.e. Soil Plant Analysis Development-SPAD value) and crop growth rate were recorded for AZRC Dera sown on 10th December and treated with AA + GA + K combination in 2019-20 and 2020-21. Similarly, leaf area index, net assimilation rate, root length, grain yield and yield contributing parameters (tillers, grains/spike and thousand grains weight) were recorded in wheat variety AZRC Dera sown on 10th December and treated with K + AA. Recommendation from the experiment that sowing on 10th December, with exogenous application of K+AA and AA+GA+K foe shoot growth with inoculation of biozot for root development. So, the foliar application of AA+GA+K and inoculation with biozote at 10th December sowing is recommended as best under late sown conditions.